Measurement and Spatial Transfer of Blue Water Footprint in Urumqi-Changji-Shihezi Megalopolis——Based on MRIO Model - LYU Zhengyin; SUN Jianguang (Renmin Zhujiang)
To find a way to alleviate the pressure on water resources during the coordinated development of the Urumqi-Changji-Shihezi megalopolis,this paper calculated the blue water footprint in the megalopolis from the perspectives of production and consumption with a city-scale multi-region input-output (MRIO) model.The pattern of spatial transfer among the sectors of the region and between the region and the rest of the country was also measured.The results lead to the following conclusions:① In 2012,the blue water footprint of production in the Urumqi-Changji-Shihezi megalopolis was 3.383 billion m3,mainly due to the large production scale of the agriculture,forestry,animal husbandry,and fishery in Changji.In contrast,the blue water footprint of consumption was as high as 6.403 billion m3 because Urumqi and Shihezi imported a lot of blue water footprint in the primary industry (mainly from inside Xinjiang) and the tertiary industry (mainly from outside Xinjiang).② The self-sufficiency of the Urumqi-Changji-Shihezi megalopolis is limited.Nevertheless,the various sectors of each city are closely related to each other,and those in Shihezi are especially prominent in pulling the region's water consumption up to a high level.③ The Urumqi-Changji-Shihezi megalopolis has a net import of blue water footprint from within Xinjiang that is higher than its net export to outside Xinjiang.Specifically,Urumqi achieves a net import from both inside and outside Xinjiang and has a net export only in the sectors of petroleum,coking products,and processed nuclear fuel products.In contrast,Changji,presenting itself with a net export,and Shihezi,with a net import,rely on the inflow from the primary and tertiary industries within Xinjiang on the one hand and are burdened with the demand of major agricultural provinces outside Xinjiang and the developed provinces and cities in Southeast China for agricultural and livestock products and primary industrial products on the other hand.This research can thus provide a reference for the rational allocation of water resources in the Urumqi-Changji-Shihezi megalopolis and the strategic arrangement for foreign trade.